Projeto e desenvolvimento de um sistema de medição sem contato aplicado ao processo de torneamento - Silva, Rafael Franklin Alves (2011)
This work presents a non contact measurement techniques study on the manufacturing process and the design and development of a non contact measurement system for inspection of diameters of parts during the machining process on the lathe. Amongst the techniques are showed technologies which are based on physical principles of optical, pneumatic, electric or ultrasound. The system developed to this work uses an optical sensor to take the scan on the part and an incremental rotary encoder to monitor the displacement of that one. At the end of the inspection operation, the diameter of the part is indicated on a display and transmitted to the computer to standard RS-232 serial communication. Test with the developed measurement system were realized such in the laboratory like a machine shop environment in order to determine the metrological characteristics of the prototype in different conditions of operation. Based on experiments with non contact measuring system, it presented good repeatability, reproducibility and long term stability.